2003
DOI: 10.1136/bjo.87.12.1497
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-103 plaque radiation therapy for macular degeneration: results of a 7 year study

Abstract: Aim: To report 7 year results of ophthalmic plaque radiotherapy for exudative macular degeneration. Methods: In a phase I clinical trial, 30 patients (31 eyes) were treated with ophthalmic plaque irradiation for subfoveal exudative macular degeneration. Radiation was delivered to a mean 2 mm from the inner sclera (range 1.2-2.4) prescription point calculated along the central axis of the plaque. The mean prescription dose was 17.62 Gy (range 12.5-24) delivered over 34 hours (range 18-65). Early Treatment Diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 52 publications
0
32
1
3
Order By: Relevance
“…Flaxel et al [17] treated patients with CNV with either 8 or 14 cobalt gray equivalents of protons and found that 14 cobalt gray equivalents seemed to inhibit the growth of CNV and stabilize VA, but that it lead to a high incidence of radiation retinopathy (44%). Plaque-based brachytherapy has been employed with mixed results (only short-term benefit in 1 study, with 45% long-term stabilization of VA in another) [18,19] .…”
Section: Discussionmentioning
confidence: 99%
“…Flaxel et al [17] treated patients with CNV with either 8 or 14 cobalt gray equivalents of protons and found that 14 cobalt gray equivalents seemed to inhibit the growth of CNV and stabilize VA, but that it lead to a high incidence of radiation retinopathy (44%). Plaque-based brachytherapy has been employed with mixed results (only short-term benefit in 1 study, with 45% long-term stabilization of VA in another) [18,19] .…”
Section: Discussionmentioning
confidence: 99%
“…Studien zur primären episkleralen Brachytherapie bei AMD sind mit StrontiumApplikatoren ( 90 Sr/ 90 Y) [17,18] und Palladium-Applikatoren ( 103 Pa) [9,10] durchgeführt worden; 106 Ru/ 106 Rh-Applikatoren sind vereinzelt eigesetzt worden, ohne dass daraus eindeutige Daten abzuleiten wären [29].…”
Section: Episklerale Brachytherapieunclassified
“…Die von Finger al. publizierten Langzeitergebnisse nach Brachytherapie mit einem 103 Pa Applikator (10-122 mm breit; mittlere Dosis im Zielvolumen 17,62 Gray) konnten zeigen, dass es nach Brachytherapie zu einer deutlichen Rückbildung exsudativer Veränderun-gen kommt; ein Vorteil in Bezug auf eine bessere Funktion konnte allerdings nicht nachgewiesen werden [10].…”
Section: Episklerale Brachytherapieunclassified
“…103 Pa is a (bitte griechisches gamma einsetzen)-emitter with a photon energy of 21 kV (compared to 28 kV for 125 I) with a lower tissue penetration compared to 125 I. Long-term results with a 103 Pa plaque were able to demonstrate a reduction of the exudation but no improvement in function [8]. 90 Sr is a β-emitter with a decay energy of 0.55 MeV and a half life of 27.78 years that decays to 90 Y with a decay energy of 2.27 MeV.…”
mentioning
confidence: 90%
“…Brachytherapy can be applied using either episcleral [8,9] or epiretinal applicators via a pars plana approach [10].…”
mentioning
confidence: 99%